LITERASI MEDIA: KEGIATAN LITERASI MEDIA BARU DI MEDIA SOSIAL (STUDI KASUS PADA SISWA SMKN 49 JAKARTA UTARA) - Muthia Rahayu; Engga Probi Endri (Jurnal Ranah Komunikasi, 2023)
At SMKN 49, Marunda, digital literacy activities are carried out to fulfill school assignments. Assignments must be uploaded to social media, one of which is Instagram, and must be tagged by the teacher so that the teacher can see and assess the assignment. According to data from the 2016 Most Littered Nation in The World study, interest in reading in Indonesia is very low. Now that the digital world is growing rapidly, all information is comprehensive by accessing it on gadgets. People are increasingly not interested in print media, as well as with high school students, where teenagers are very enthusiastic about using the internet. This study uses Eschet Alkalai's theory regarding 5 digital literacy skills and analysis of media literacy programs, namely, the dimensions of motivation, knowledge and skills. Using a qualitative case study methodology with a constructivist paradigm. The results of this study are that the new media literacy activities carried out by SMKN 49 are quite good by using social media as a medium for literacy. Giving assignments that 'force' students to read from the internet, which can trigger students to read and search for information from the internet and increase studentcreativity